Globalization and Forces for Change in Higher Education - Altbach, Philip (International Higher Education, 2008)
For higher education, globalization implies the broad social, economic, and technological forces that shape the realities of the 21st century. Massification is without question the most ubiquitous global influence of the past half century or more. It brought themes regarding, public and private good, access, differentiation, and varied funding patterns, and declining of quality and conditions of study. The growth of information technology (IT) and the increasing dominance of English as the key language of communicating academic knowledge are also key elements of globalization.